Heat-Assisted Pulsed Electric Field Treatment for the Inactivation of Saccharomyces cerevisiae: Effects of the Presence of Citral - Montanari, Chiara; Tylewicz, Urszula; Tabanelli, Giulia; Berardinelli, Annachiara; Rocculi, Pietro; Ragni, Luigi; Gardini, Fausto (Frontiers in Microbiology, 2019)
Pulsed electric field (PEF) treatment is a non-thermal technology that has shown good potential for microbial inactivation. However, in many cases, it cannot be sufficient to avoid microbial proliferation and the combination with other stabilizing technologies is needed. In the framework of the hurdle concept, several researches have been focused on the use of PEF in combination with heat and/or antimicrobials to increase its efficacy. This study investigated the inactivation effect of PEF on a strain of Saccharomyces cerevisiae (isolated from spoiled beverages) in a model system (growth medium). The efficacy of PEF treatment was evaluated in relation to different variables, such as electric field strength (25 and 50 kV/cm), treatment time (from 1 to 5 seconds), initial inoculum level (4 or 6 log cfu/ml), pre-heating at 50°C, medium pH (4 or 6) and addition of citral at sub lethal concentration (i.e. half of minimum inhibiting concentration). The data from plate counting, modelled with the Weibull equation, showed that one of the main factors affecting yeast inactivation was the pre-heating of the suspension at 50°C. Indeed, higher cell load reductions were obtained with heat-assisted PEF, especially in the presence of citral. The effect of initial cell load was negligible, while pH affected yeast inactivation only without pre-heating, with higher death kinetics at pH 6. Flow cytometry (FCM) analysis confirmed higher mortality under these conditions. However, the occurrence of injured cells, especially in samples treated at pH 4, was observed. The ability of these cells to recover from the damages induced by treatments was affected by both citral and pre-heating. The synergic effects of PEF, pre-heating and citral were likely due to the increase of membrane permeability (especially at pH 6), as the primary target of electroporation, which favoured the solubilization of citral in the cell membrane, enhancing the efficacy of the whole process. The multi-analytical approach (traditional plate counting and FCM) allowed defining parameters to increase PEF efficacy against S. cerevisiae. Moreover, FCM, able to discriminate different physiological states of the yeast population, was helpful to better clarify the action mechanism and the potential recovery of cells after treatment.